1980
DOI: 10.1038/284531a0
|View full text |Cite
|
Sign up to set email alerts
|

2H NMR study of molecular motion in collagen fibrils

Abstract: Collagen was labelled through tissue culture with [3,3,3-d3]alanine. 2HNMR spectra were obtained of the labelled collagen as fibrils and in solution using the quadrupolar echo technique for solids. The 2H NMR data were analysed in terms of a model for reorientation in which the molecule is considered to jump between two orientations in a time which is short compared to the residence time in each site, and short compared to (delta vq)-1. The best fit of the data indicates that the collagen molecule in the fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 17 publications
2
85
0
Order By: Relevance
“…In contrast, the liquid-crystalline model for collagen (35) suggests a significant degree of disorder, especially in the collagen fiber gap regions. In addition, nuclear magnetic resonance studies indicate a considerable degree of rotational freedom for individual molecules in the collagen fiber (36). The distribution of binding sites for SPARC, DDR2, and VWF along the collagen circumference supports the notion of considerable flexibility within the collagen fibril.…”
Section: Resultsmentioning
confidence: 74%
“…In contrast, the liquid-crystalline model for collagen (35) suggests a significant degree of disorder, especially in the collagen fiber gap regions. In addition, nuclear magnetic resonance studies indicate a considerable degree of rotational freedom for individual molecules in the collagen fiber (36). The distribution of binding sites for SPARC, DDR2, and VWF along the collagen circumference supports the notion of considerable flexibility within the collagen fibril.…”
Section: Resultsmentioning
confidence: 74%
“…Previous 2H and 13C NMR studies of labeled collagen fibrils have shown that rapid, r-=10-s, reorientation of the peptide backbone occurs about the long axis ofthe helix through an angle of ca. 300 (1)(2)(3)(4). These studies also have provided strong evidence that the amino acid side chains exhibit extensive internal motions in the fibrils (3,5 (9) that accounts for spectral distortion due to a finite pulse width.…”
mentioning
confidence: 74%
“…Line shape analysis has most widely been used in 2 H NMR for various reasons: i) spectral interpreta-tion is facilitated since the 2 H gradient field tensor is almost perfectly axially symmetric for most CD bonds and its unique principal axis aligned with the CD vector within 38 (59,120); ii) quadrupole splittings of 2 H are about 200 kHz (116,121) and spectra are therefore sensitive to motions with correlation times shorter than the ms; iii) finally, in addition to cell culture specific labeling, fibers can sometimes be 2 H-labeled by extensive soaking in D 2 O (19, 116). 2 H spectra are recorded using the solid echo technique to correct phasing and baseline problems due to receiver dead time (122).…”
Section: Signal Intensity Line Width and Line Shape Analysismentioning
confidence: 99%
“…First, 2 H NMR spectra of alanine-labeled collagen were analyzed by Jelinski et al (120) according to a model in which the fiber backbone undergoes rapid reorientation about the long axis of the molecule. By fitting the experimental spectra with calculated spectra based on a two-site jump model, the reorientation angle was determined to be of $308 (120,123) and the average angle between the alanine C a -C b bond axis and long axis of the collagen helix was estimated to be $758 (123). In addition, the motion of leucine side chains in collagen was also evidenced by 2 H NMR and could be explained by a fast exchange between two predominant conformations (123,124).…”
Section: Signal Intensity Line Width and Line Shape Analysismentioning
confidence: 99%